Molecular genetic features and clinical manifestations in Chinese familial cerebral cavernous malformation: from a novel KRIT1/CCM1 mutation (c.1119dupT) to an overall view - Chen, Yanming; Dong, Xuchen; Wang, Ye; Lv, Haijun; Chen, Nan; Wang, Zhongyong; Chen, Si; Chen, Ping; Xiao, Sheng; Zhao, Jizong; Dong, Jun (Frontiers in Neuroscience, 2023)
Cerebral cavernous malformations (CCMs) are common vascular anomaly diseases in the central nervous system associated with seizures, cerebral microbleeds, or asymptomatic mostly. CCMs can be classified as sporadic or familial, with familial cerebral cavernous malformations (fCCMs) being the autosomal dominant manner with incomplete penetrance. Germline mutations of KRIT1, CCM2, and PDCD10 are associated with the pathogenesis of fCCMs. Till now, little is known about the fCCMs mutation spectrum in the Han Chinese population. In this study, we enrolled a large, aggregated family, 11/26 of the family members were diagnosed with CCMs by pathological or neuroradiological examination, with a high percentage (5/9) of focal spinal cord involvement. Genomic DNA sequencing verified a novel duplication mutation (c.1119dupT, p.L374Sfs*9) in exon 9 of the Krev interaction trapped 1 (KRIT1) gene. The mutation causes a frameshift and is predicted to generate a truncated KRIT1/CCM1 protein of 381 amino acids. All our findings confirm that c.1119dupT mutation of KRIT1 is associated with fCCMs, which enriched the CCM genes’ mutational spectrum in the Chinese population and will be beneficial for deep insight into the pathogenesis of Chinese fCCMs. Additionally, with a retrospective study, we analyzed the molecular genetic features of Chinese fCCMs, most of the Chinese fCCMs variants are in the KRIT1 gene, and all these variants result in the functional deletion or insufficiency of the C-terminal FERM domain of the KRIT1 protein.